Weaving networks between the University and the territory: the experience of the Mauricio López Project, Uniendo Brazos (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
The present work seeks to look back at the experience of university extension work carried out during the year 2019 in the frame of the Uniendo Brazos Project, financed by the 11th Mauricio López Call for Proposals, from Universidad Nacional de Cuyo. We will begin by reflecting on what we understand by extension and our way of approaching it in the territory. Then we will make a brief description of the Los Peques solidarity canteen, where the project took place, and a revision of the relationships that we built with the women who manage it. Finally, we will highlight the most relevant experiences and meanings in order to rethink the knowledge we have learned, through an exercise of theorisation and conscious appropriation of what we have experienced throughout the year.
Keywords: University extension work; collective knowledge building; knowledge dialogue; migrant women; solidarity canteen